Opportunities and Challenges of Using Generative AI in English Writing Learning in Higher Education - Shomad Al-Ilmi, Moh. Bastuta; Rosyidah, Azizatur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to critically examine the impact of AI utilization, not only in terms of its technical benefits in improving writing skills, but also its impact on students' analytical thinking skills, originality of work, and academic integrity. This study also offers new perspectives for higher education institutions in formulating policies, ethical guidelines, and learning strategies that integrate AI while still strengthening students' independent competencies. The research method used is a qualitative descriptive approach with a literature review, which collected relevant information and scientific works from books, journal articles, and other scientific writings. The results indicate that AI plays a significant role as an effective tool in the writing process, such as assisting with vocabulary selection, checking grammar, and providing suggestions for improvement. AI also functions as a personal, efficient, and interactive partner in English learning. The strategy for effective AI utilization is to make it an aid, not a substitute for personal effort, with the awareness that AI should be used wisely to improve writing and not to replace personal understanding. The study concludes that while AI offers significant opportunities, adaptation and ethical challenges remain major concerns, emphasizing the central role of educators in the learning process.